A Modified Unified Theory of Acceptance and Use of Technology (UTAUT)Model in E- Learning Adoption by Students in the Nigerian Higher Educational Institutions (HEIs): A Conceptual Paper - Adeyemo, Oluwaseyi A; Babalola, Gbemisola O. (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
The world is changing today because of the impact of Information and Communications Technology (lCT) in all aspects of human endeavours including learning and education. In fact, Higher Education Institutions (HEls) in developed countries believe that these developments offer rich opportunities to embed technologicalinnovations within the leaming environment (Al-Adwan et aI, 2013). However, a lot of Higher Education Institutions (HEls) in Nigeria are yet to implement e-Leaming for various reasons even though there have been improvements in the use of the web for other opportunities and purposes like course registration and fee payments by the students. Furthermore, little or no research has been carried out to determine why the adoption of e-leaming is still very low on the part of the students in the HEls that have implemented it. Hence, in this paper we propose a conceptual framework of a modified Unified Theory of Acceptance and Use of Technology (UTAUT) model towards investigating the adoption of e-leaming by students in the Nigerian HEls.